Ferrite Core‐Shell Nanoparticles Synthesized by Seed‐Based Method Characterization and Potential Application. Issue 16 (10th June 2018) - Klekotka, Urszula; Piotrowska, Beata; Satuła, Dariusz; Giersig, Michael; Kalska‐Szostko, Beata
Abstract : This paper is dedicated to a systematic study on the selected type of core‐shell magnetic nanoparticles. Described fabrication procedure adopts the idea of seeds‐based synthesis followed by subsequent layer growth. Each layer of formed particles is obtained from complexes of M(acac) x, where M stands for 3d elements (Fe, Co, Ni, Mn) and x is equal to 2 or 3 resulting in oxide formation. Obtained core‐shell nanoparticles are structurally examined by X‐ray diffraction, infra‐red spectroscopy, and transmission electron microscopy. Magnetic properties of the proposed nanoparticles are tested by Mössbauer spectroscopy. Variable in layered manner composition allows for tuning of physicochemical properties of the investigated material. Designed on demand layer‐by‐layer growth gives the opportunity to obtain desired final properties of, for example, sensing character or selectivity of interacting spices. Abstract : This work shows synthesis and characterization of core‐shell magnetic nanoparticles, where, each layer is composed of different oxides (iron, cobalt, nickel, or manganese). Nanoparticles are obtained by modified thermal decomposition of metal acetylacetonate precursor. Changes in layered manner composition allows for tuning physicochemical properties of the final material. Designed on demand layer‐by‐layer growth gives the opportunity to obtain desired final properties.